2005
DOI: 10.4049/jimmunol.175.3.1643
|View full text |Cite
|
Sign up to set email alerts
|

TLR-4 Regulates CD8+ T Cell Trapping in the Liver

Abstract: Mammalian TLRs are understood primarily as an activating system for innate and adaptive immunity, but have also been implicated in sensing cellular damage and in promoting intestinal integrity. In this study we show that TLR-4 also controls the in vivo distribution of activated CD8+ T cells. The liver is a site for trapping and apoptosis of activated CD8+ T cells during systemic immune responses, but the reason for this is unknown. In this study we tested the hypothesis that the liver’s constant exposure to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 33 publications
(21 reference statements)
1
47
1
Order By: Relevance
“…In mice, Con A induces a severe liver injury that is a model of human T-cell-mediated hepatitis, which is dependent on the activation of CD4 þ lymphocytes (3) and requires Th1 cytokines such as IL-2, IFN-g, and TNF-a. It is reported that deficiency of Toll signaling resulted in failure to generate Th1-dependent immune responses (16), and TLR4 also plays vital roles in the function of CD4 þ and CD8 þ T cells (17,18). Using antibiotics to reduce the LPS levels and TLR4 knockout mice, we showed that gut-derived LPS can promote Con A-induced liver injury in TLR4-dependent manner.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In mice, Con A induces a severe liver injury that is a model of human T-cell-mediated hepatitis, which is dependent on the activation of CD4 þ lymphocytes (3) and requires Th1 cytokines such as IL-2, IFN-g, and TNF-a. It is reported that deficiency of Toll signaling resulted in failure to generate Th1-dependent immune responses (16), and TLR4 also plays vital roles in the function of CD4 þ and CD8 þ T cells (17,18). Using antibiotics to reduce the LPS levels and TLR4 knockout mice, we showed that gut-derived LPS can promote Con A-induced liver injury in TLR4-dependent manner.…”
Section: Discussionmentioning
confidence: 85%
“…TLR4 was also expressed on T lymphocyte, playing a vital role in adaptive immunity. Recent studies have shown the contribution of TLR4 signaling to the trapping of CD8 þ T cells within the murine liver (17).…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no overt accumulation of KIR ϩ CD8 ϩ or NKG2A ϩ CD8 ϩ T cells in the patients, our results indicate that within the liver, the frequency of NKG2A ϩ CD8 ϩ T cells, but not KIR ϩ CD8 ϩ T cells, correlates with lesion severity. The increased frequency of NKG2A ϩ CD8 ϩ T cells that we found in liver samples with marked lesion severity could possibly be related to the fact that the liver can retain committed CD8 ϩ T cells, [39][40][41] a phenomenon that could be reinforced during chronic inflammation. In theory, liver NKG2A ϩ CD8 ϩ T cells could contribute to lesions because some of them were perforin ϩ and there were blasting cells with a high forward scatter (FSC high ) (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The role of liver and spleen in the pathogenesis of various immune-mediated diseases is well known [17,18,30]. Results of a previously published study [30] suggest that the liver is involved in immune modulation by intrahepatic trapping of CD8 + cells and dual function of NK and NKT cells.…”
Section: Discussionmentioning
confidence: 96%